Relationship between the primary tumor (T), regional lymph nodes (N) and metartasis distance (M) in the clinical staging of breast cancer - Díaz Plasencia, Juan (2015)
This retrospective study evaluated the relationship between factors according to TNM clinical classification proposed by the UICC in 1987 in 122 patients with histologically confirmed breast cancer overlooking Bethlehem Hospital from 1966 to 1983. The mean age was 48.4 ± 11.9 years (range, 23-87 years). The fifth decade was the most affected (36.1%) and 62 patients (50.8%) were premenopausal. The TE medium was 12.5 months (range, 12 days to 10 years), the most frequent symptoms were breast lump (95.1%), breast tenderness (40.9%), skin redness (13.1%) and haematological Nipple discharge (6.5%) . Clinical signs were diagnosis: tumor (99.1%), axillary lymph node (46.7%), retraction of the nipple (33.6%) and orange peel (18.8%). The most frequently committed neoplasia left breast (55.8%) than the right (44.2%); and it was located in the CSE in 54.1% of cases, 21.3% CSI, CIE 8.2%, the entire breast in 7.4%, the central region at 5.7% and 3.3% IIC . Of the 122 patients, 3 (2.5%) were in EC-0, 8 (6.6%) in CD-I, 33 (27.0%) in EC II-A, 34 (27.9%) in EC II-B, 12 ( 9.8%) in EC III-A, 17 (13.9%) in EC III-B and 15 (12.3%) in EC IV. Fifteen patients (12.3%) presented MAD, the most frequent sites: lung (53.3%), pleura (26.6%), supraclavicular lymph node (33.3%), peritoneum (13.3) and bone (6.6%). There were statistically significant direct relationship between T and N (p <0.001) and the incidence of M (p <0.001). There was also significant direct relationship between N and M (p <0.002). Conclude that there is correlation between T. N and M, and clinical staging is important because it helps to plan treatment, it is prognostic value and facilitates the exchange of information between various centers.